Effect of feeding semi-moist diet as a practical strategy to reduce feed costs in tilapia juvenile production - Honorato L.* (2023)
© 2023, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.Tilapia (Oreochromis niloticus) is one of the species with the greatest increase in production worldwide. However, the continuous increase in the price of ingredients, and consequently in the diet costs may limit the expansion of the sector. Several alternatives to reduce feed costs are currently under study, as the use of practical press-pellet semi-moist diet that can be manufactured on farm. This study evaluates five levels of replacement (0, 25, 50, 75, and 100%) of a commercial diet by a practical (press-pellet semi-moist) diet and its effect on zootechnical performance, carcass proximate composition, as well as somatic and economic indexes in tilapia juveniles (9.48 g). After 56 days, survival and condition factor did not differ significantly between treatments. Final weight, daily weight gain, feed conversion, and specific growth rate had a negative linear effect as the practical diet increased, while carcass yield had a positive linear effect. Carcass crude protein content was higher in fish fed with 100% practical diet, while crude lipid had the lowest content in this same treatment. As for economic indexes, the estimated cost of feeding decreased as a function of the practical diet inclusion, with a final saving of US$ 8.68 per thousand of juveniles produced (100% replacement).